Evaluating Performance Quality of Physical Education and Scouting Departments in Baghdad's Education General Directorates from Physical educators Point of View - Reja Abdul Hussein Aziz; Asaad Abdulla Alsalami (College of Physical Education and Sport Sciences, 2021)
The research aimed at constructing a quality performance scale for physical education and scouting activities departments in Baghdad general education directories of education from physical educators' point of view as well as identifying the level of performance quality of physical education and scouting activities departments in Baghdad general education directories. The problem of the research lies in answering the following questions: what is the current level of physical education and scouting department performance quality in Baghdad general directorates of education from physical educators' point of view? What is the main reason that helped positive or negative performance? Is quality performance evaluation effective for identifying this performance and its level? The researchers used the descriptive method on (472) secondary school physical educators and the subjects were (317) that were divided into the pilot study, construction, and application subjects. The researchers proposed (22) items for measurement and the data was collected and treated using proper statistical operations to come up with the conclusions and recommendations.